Hydrogen gas production from glycerol via steam reforming using nickel loaded zeolite catalyst - Azaman, Fazureen; Juahir, Hafizan; Mohamed, Mahadhir; Azid, Azman; Yunus, Kamaruzzaman; Abdul Rahman, Anis Farhana; Wan Ranizang, Wan Nur Anis Amira; Md Sanin, Fara Aiza; Amran, Mohammad Azizi; Zainal Abidin, Mohd Zaid Arqam; Hairoma, Norsyuhada; Sulaiman, Nur Hishaam; et al. (Universiti Kebangsaan Malaysia (UKM), 2015)
Glycerol is the main by-product of biodiesel production that produces from transesterification process. In this research, focused was on hydrogen production via glycerol steam reforming using nickel loaded HZSM-5 catalyst. The catalysts were prepared by using different loading amount of nickel (0.5, 1.0, 5.0, 10.0 and 15 wt %) on HZSM-5 catalyst through the wet impregnation method at temperature 500 ºC and atmospheric pressure. The catalyst was characterized by using XRD, FTIR and SEM. Then, only 15 wt % Ni loading has been chosen based on the parameter which is different range of catalyst weight (0.3-0.5g) at different range of glycerol flow rate (0.2-0.4mL/min) at temperature 600 ºC and atmospheric pressure. The products were analyzed by using gas-chromatography with thermal conductivity detector (GC-TCD) where it is used to identify the yield of hydrogen. The data of the experiment were analyzed by using Response Surface Methodology (RSM) in order to study the relationship of catalyst weight and glycerol flow rate. The results showed that the optimum condition to produce a maximum hydrogen yield with 15wt% Ni/HZSM-5 catalyst was 78.10004% at glycerol flow rate of 0.356484 mL/min and catalyst weight of 0.429267 g.